Penggunaan Exploratory Factor Analysis (EFA) sebagai Analisis Faktor-faktor Stres Akademik Pada Mahasiswa - Fitriani, Aura Syfa; Susanti, Roza Eva; Ersya, Miftahur Raihan; Ibadullah Poeni, Muhammad Abiyu; Afifah, Syifa; Nudhar, Azarine (Universitas Negeri Padang, 2024)
Academic stress is a condition that occurs when a person faces excessive and unachievable demands in an educational environment. This study aims to analyze the factors of academic stress in college students. The research method used is a quantitative method with a research sample of 206 active students in Indonesia. The sampling technique used was incidental sampling. Data were collected through an online questionnaire using a five-point Likert scale. Data analysis was conducted using exploratory factor analysis (EFA) with principal component factor reduction method and varimax rotation. The results obtained five factors that form academic stress in students, including relationship factors with others, fatigue factors, self-adjustment factors, conflict factors and economic factors.